Turki dalam Pencarian Bentuk Pemerintahan (Sebuah Catatan Sejarah) - Abd Rahman R (Rihlah : Jurnal Sejarah dan Kebudayaan, 2014)
Turkey was founded by Qayigh Oghus than one child Turkish tribes who inhabit the west Gobi, or local country Mongols and northern regions of China, led by Solomon. Royal Ottoman territory from time to time increasingly expanding to include several regions of three continents, Africa, Asia, and Europe. Kingdom of the Ottoman get the support of a formidable military force. Ottoman empire is one of the oldest Islamic government to survive the experience ups surut.Pemerintahan Ottoman Empire led by a caliph, who has the power, in addition to religious leaders, as well as head of state, which is subsequently transformed into a republic, the caliph as a religious leader eliminated and also the sultan as the head of state dispensed replaced by a government led by a head of state is called the president. Government of the Ottoman Empire in running government aided by large vizier and some ministers who run government services.